Earlier stage for straggler detection and handling using combined CPU test and LATE methodology - Anwar H. Katrawi; Rosni Abdullah; Mohammed Anbar; Ammar Kamal Abasi (Institute of Advanced Engineering and Science, 2020)
Using MapReduce in Hadoop helps in lowering the execution time and power consumption for large scale data. However, there can be a delay in job processing in circumstances where tasks are assigned to bad or congested machines called